Understanding Stakeholder Views Regarding the Design of an Intervention Trial to Reduce Anticholinergic Burden: A Qualitative Study - Cunningham, Yvonne; Wood, Karen; Stewart, Carrie; Nakham, Athagran; Newlands, Rumana; Gallacher, Katie I.; Quinn, Terence J.; Ellis, Graham; Lowrie, Richard; Myint, Phyo Kyaw; Bond, Christine; Mair, Frances S. (Frontiers in Pharmacology, 2021)
Background: Anticholinergic burden (ACB), is the cumulative effect of anticholinergic medication which are widely prescribed to older adults despite increasing ACB being associated with adverse effects such as: falls, dementia and increased mortality. This research explores views of health care professionals (HCPs) and patients on a planned trial to reduce ACB by stopping/switching anticholinergic medications. Objectives were to explore views of key stakeholders (patients, public, and HCPs) regarding the potential acceptability, design and conduct of an ACB reduction trial. Materials and Methods: Qualitative interviews and focus groups with 25 HCPs involved in prescribing medication with anticholinergic properties and with 22 members of the public and patients who were prescribed with the medication. Topic guides explored aspects of feasibility including: 1) views of a trial of de-prescribing/medication switching; 2) how to best communicate information about such a trial; 3) views on who would be best placed and preferred to undertake such medication changes, e.g. pharmacists or General Practitioners (GPs)? 4) perceived barriers and facilitators to trial participation and the smooth conduct of a trial; 5) HCP views on the future implementability of this approach to reducing ACB and 6) patients’ willingness to be contacted for participation in future trials. Qualitative data analysis was underpinned by Normalization Process Theory. Results: The public, patients and HCPs supported an ACB reduction trial. There was consensus among the groups that key points to consider with such a trial included: 1) ensuring patient engagement throughout to enable concerns/potential pitfalls to be addressed from the beginning; 2) ensuring clear communication to minimise potential misconceptions about the reasons for ACB reduction, 3) providing access to a point of contact for patients throughout the life of a trial to address concerns; The HCPs in particular also suggested: 4) minimise workload implications of any trial; and 5) pharmacists may be best placed to carry out ACB reviews, though overall responsibility for patient medication should remain with GPs. Conclusion: Patients, the public and HCPs support trials to reduce ACB. Good communication and patient engagement during design and delivery of a trial are essential as is safety netting and minimising workload.